INTEGRATION OF CHARACTER VALUES IN LEARNING AKIDAH AKHLAK AT MADRASAH IBTIDAIYAH INTEGRAL AL UKHUWWAH BANJANG - Husin Husin (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2020)
This study aims to determine the integration of character values in learning Akidah Akhlak at Madrasah Ibtidaiyah Al Ukhuwwah, Banjang District, Hulu Sungai Utara Regency and how it is implemented in children's daily lives.This study used a qualitative method with the type of narrative research and data collection through observation, document review and interviews with school principals and teachers of Akidah Akhlak subjects.In the interview process, the researcher also conducted a depth interview on the important points obtained in the initial interview process. In the cognitive aspect, teacher assessments include oral tests, practice scores, assignments, homework (PR) and daily test scores, on the psychomotor aspect, teacher assessments include students' skills to demonstrate the value of caring for others in front of the class, on the affective aspect, teachers assess students who actively participate in class discussions. This research contributes to the study of the integration of character values in various lessons so that in its implementation it can be used as an example or modified according to the needs of the learning process that has been designed by the teacher and adapted to the established learning model and strategy.